Operations management international student edition with global reading - Stevenson, William J. (McGraw-Hill/Irwin series operations and decision sciences., 2007)
Features the latest concepts and applications while not losing focus on the core concepts that has made this text a market leader. This approachable text supports students in applying concepts and methods by providing solved problems, examples, questions, practice problems, and cases.